Human commensal gut Proteobacteria withstand type VI secretion attacks through immunity protein-independent mechanisms - Nicolas Flaugnatti (Nature Portfolio, 2021)
Here, the authors study the impact of Vibrio cholerae’s T6SS on human gut microbiota isolates and show that certain bacteria are protected from T6SS attacks in an immunity protein-independent manner. Specifically, protection occurred through superior T6SS weaponry in members of the Enterobacter cloacae complex and by molecular armors made of membrane-tethered capsular polysaccharides of diverse Klebsiella isolates.